Rancang Bangun Laser Grafir Portabel Berdaya Rendah Pada Media Kayu - Hisyam Ma’mun; Gostsa Khusnun Naufal; Agus Mukhtar (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
Wood can be increased in value by adding patterns using light from a laser. The types of laser sources which are currently divided into 4 types include: Semiconductor lasers, Solid-state lasers, Fiber lasers, Gas lasers. Each laser generation source has differences in the way the laser light is generated, the laser wavelength produced and the supporting components needed to operate the laser system. In this research, the type of laser source will be selected according to the criteria determined by the researcher. The selection was carried out using the decision matrix method, with the highest number of values obtained from the Semiconductor lasers type laser source. Followed by testing the laser components into the available wood media. The results obtained by the laser system are in accordance with the criteria set by the researchers